Analisis Yuridis Penolakan Notaris dalam Pembuatan Akta Autentik (Studi di Kota Medan) - Rizka Azizah Siregar; Keizerina Devi Azwar; Suprayitno Suprayitno (Universitas Medan Area, 2022)
Article 1 point (1) of Law No. 2 of 2014 on Amendments to Law No. 30 of 2004 concerning Notary Positions, Notaries are general officials who are authorized to make authentic deeds and other authorities as referred to in this Law. Notaries are obliged to provide services in accordance with the provisions of this Act, unless there is a reason to refuse them. So this study intends to know and analyze the legal arrangements of Notaries in rejecting the creation of authentic deeds, the reason notaries for rejection in the creation of authentic deeds in the city of Medan, and the legal consequences for Notaries who refuse the creation of authentic deeds. This type of research uses empirical juridical research that is descriptive analytical. From the results of the research it is known that the notary legal arrangement to reject the creation of authentic deeds, namely Article 16 paragraph (1) letter e UUJN, The Reason notaries in Medan city for rejection in the creation of authentic deeds both for reasons as explained.